Uji Hedonik Pasta Fettuccine Aglio E Olio Subtitusi Tepung Ubi Garut - Sophia Indira Wibowo; Sulih Wahyudiono (LPPM and Travel Operation Department Universitas Asa Indonesia, 2024)
Abstract Pasta Fettuccine Aglio e Olio is a dish originating from Italy. This dish is quite famous in various parts of the world, one of which is Indonesia. The combination of Fettuccine Pasta cooked with garlic sauce and olive oil makes this dish popular among all ages. In this research, an innovation will be carried out in the form of substituting wheat flour for pasta using arrowroot tuber flour in percentages of 25%, 50% and 75%. This research uses a hedonic test, to determine the level of respondents' preferences for color, taste, aroma and texture. The research instrument used was a questionnaire which was distributed to 42 University Asa Indonesia Grand Chef School students, Class of 2021. From the distribution data, the results obtained were that in terms of color, respondents chose product (P3) with an average of 3.04, then in terms of texture, respondents chose product (P4) with an average of 3, in terms of aroma, respondents chose product (P3) and (P4) with an average size of 2.61 and in terms of taste, respondents chose product (P3) with an average size of 2.88. This shows that Fettuccine Aglio e Olio Pasta which is substituted with arrowroot tuber flour has the potential to be liked by public